Activation of Cdk5/p25 and tau phosphorylation following chronic brain hypoperfusion in rats involves microRNA‐195 down‐regulation. (7th August 2015) - Sun, Li‐Hua; Ban, Tao; Liu, Cheng‐Di; Chen, Qing‐Xin; Wang, Xu; Yan, Mei‐Ling; Hu, Xue‐Ling; Su, Xiao‐Lin; Bao, Ya‐Nan; Sun, Lin‐Lin; Zhao, Lin‐Jing; Pei, Shuang‐Chao; et al.
Abstract: Chronic brain hypoperfusion (CBH) is a common clinical feature of Alzheimer's disease and vascular dementia, but the underlying molecular mechanism is unclear. Our previous study reported that the down‐regulation of microRNA‐195 ( miR‐195 ) promotes amyloidogenesis via regulation of amyloid precursor protein and β‐site amyloid precursor protein cleaving enzyme 1 (BACE1) expression at the post‐transcriptional level in CBH rats with bilateral common carotid artery occlusion (2VO). CBH owing to unilateral common carotid artery occlusion (UCCAO) increases tau phosphorylation levels at multiple phosphorylation sites in the brain, but the molecular mechanism is poorly understood. The purpose of this study was to investigate whether miR‐195 could both deregulate amyloid metabolism and indirectly deregulate tau phosphorylation in CBH. We observed that 2VO leads to tau hyperphosphorylation at Ser202/Thr205, Ser262, Thr231, and Ser422 and to the conversion from cyclin‐dependent kinase 5 (Cdk5)/p35 to Cdk5/p25 in rat hippocampi. Endogenous miR‐195 was knocked down using over‐expression of its antisense molecule (pre‐AMO‐ miR‐195 ) via a lentivirus (lenti‐pre‐AMO‐ miR‐195 ); this knockdown increased the tau phosphorylation at Ser202/Thr205, Ser262, Thr231, Ser422, and the Cdk5/p25 activation, but over‐expression of miR‐195 using lenti‐pre‐ miR‐195 decreased the tau phosphorylation and Cdk5/p25 activation. Further in vitro studies demonstrated that miR‐195 over‐expression prevented tau hyperphosphorylation and Cdk5/p35 activity, which were increased by miR‐195 inhibition. A dual luciferase reporter assay showed that miR‐195 bound to the Cdk5r1 gene, which encodes p35 protein, in the 3′UTR and inhibited p35 expression. We concluded that tau hyperphosphorylation involves the down‐regulation of miR‐195, which is mediated by Cdk5/p25 activation in 2VO rats. Our findings demonstrated that down‐regulation of miR‐195 led to increased vulnerability via the regulation of multiple targets. Schematic diagram of miR‐195 mediated Aβ aggregation and tau hyperphosphorylation in chronic brain hypoperfusion (CBH). First, CBH results in the elevation of nuclear factor‐κB (NF‐κB), which binds with the promoter sequences of miR‐195 and negatively regulates the expression of miR‐195 . Second, down‐regulated miR‐195 induces up‐regulation of APP and BACE1 and leads to an increase in Aβ levels. Third, some of the elevated Aβ then enter the intracellular space and activate calpain, which promotes the conversion of Cdk5/p35 to Cdk5/p25 and catalyzes the degradation of IκB; IκB is an inhibitor of NF‐κB, which activates NF‐κB. Cdk5/p25 directly phosphorylates Tau. Fourth, down‐regulated miR‐195 induces an up‐regulation of p35, which provides the active substrates of p25. Our findings demonstrated that the down‐regulation of miR‐195 plays a key role in the increased vulnerability to dementia via the regulation of multiple targets following CBH. Abstract : Schematic diagram of miR‐195 mediated Aβ aggregation and tau hyperphosphorylation in chronic brain hypoperfusion (CBH). First, CBH results in the elevation of nuclear factor‐κB (NF‐κB), which binds with the promoter sequences of miR‐195 and negatively regulates the expression of miR‐195 . Second, down‐regulated miR‐195 induces up‐regulation of APP and BACE1 and leads to an increase in Aβ levels. Third, some of the elevated Aβ then enter the intracellular space and activate calpain, which promotes the conversion of Cdk5/p35 to Cdk5/p25 and catalyzes the degradation of IκB; IκB is an inhibitor of NF‐κB, which activates NF‐κB. Cdk5/p25 directly phosphorylates Tau. Fourth, down‐regulated miR‐195 induces an up‐regulation of p35, which provides the active substrates of p25. Our findings demonstrated that the down‐regulation of miR‐195 plays a key role in the increased vulnerability to dementia via the regulation of multiple targets following CBH.